NUTRITIONAL COMPOSITION OF DIOSCOREA HISPIDA FROM DIFFERENT LOCATIONS AROUND LEUSER ECOSYSTEM AREA - Sitti Saleha; Nurdin Saidi; Saiful .; Murniana .; Saida Rasnovi; Teuku M. Iqbalsyah (Universitas Syiah Kuala, 2018)
Proximate analysis of Dioscorea hispida tubers, collected from five locations around Leuser ecosystem in Aceh Province, showed variations amongst samples. Standard AOAC method for proximate analysis of the fresh weight showed that the water content varied between 15.8 - 37.8%, crude protein 1.13 -6.20%, crude lipid 1.99 - 9.36% and ash 0.29 - 1.24%. The total carbohydrate was high, i.e. between 58.3 -71.9%. The main mineral was phosphorus, with a value of 11.7 - 46.9 mg/100g. These variations could be due to soil, climate and weather factors, as well as postharvest handling. Phytochemical tests showed that all of the samples contained alkaloids and terpenoids. One of the samples (LP) also contained phenol and steroid. The high cyanide content in the tubers (379 - 739 ppm) was easily removed by repeated washing. The cyanide level dropped significantly after the 3rd wash. Information on nutritional content in D. hispida is essential for planning its utilization. Increasing the economic value of D. hispida is expected to attract people around the Leuser ecosystem to cultivate and utilize it, thereby reducing illegal forest encroachment.Keywords: Dioscorea hispida, proximate, Leuser, janeng, gadung, starchREFERENCESBarton H 2014 Yams: Origins and Development, Encyclopaedia of Global Archaeology, p 7943-7947, (Springer. DOI 10.1007/978-1-4419-0465-2_2193).Obidiegwu J E and Akpabio E M 2017 The Geography of Yam Cultivation in Southern Nigeria: Exploring Its Social Meanings and Cultural Functions J. Ethnic Foods 4 28-35.Chandrasekara A and Kumar T J 2016 Roots and Tuber Crops as Functional Foods: A Review on Phytochemical Constituents and Their Potential Health Benefits Intl. J. Food Sci. 2016 1-15.Kumar S, Das G, Shin H-S and Patra J K 2017 Dioscorea spp. (A Wild Edible Tuber): A Study on Its Ethnopharmacological Potential and Traditional Use by the Local People of Similipal Biosphere Reserve India Front. Pharmacol. 8 52.Lin J Y, Lu S, Liou Y L and Liou H L 2006a Antioxidant and Hypolipidaemic Effects of a Novel Yam–boxthorn Noodle in an In Vivo Murine Model Food Chem. 94 377–384.Lin J Y, Lu S, Liou Y L and Liou H L, 2006b, Increased IgA and IgG Serum Levels Using a Novel Yam–boxthorn Noodle in a BALB/c Mouse Model Food Chem. Toxicol. 44 170–178.Bhandari M R and Kawabata J 2004 Organic Acid, Phenolic Content and Antioxidant Activity of Wild Yam (Dioscorea spp.) Tubers of Nepal Food Chem. 88 163–168.Lin J T and Yang D J 2008 Determination of Steroidal Saponins in Different Organs of Yam (Dioscorea pseudojaponica Yamamoto) Food Chem. 108 1068–1074.AOAC 1984. Official Methods of Analysis. Washington DC: Association of Official Analytical Chemists.Harborne J B 1984 Phytochemical Method 2nd ed. (London: Chapman and Hall Ltd.)Bhandari M R, Kasai T and Kawabata J 2003 Nutritional Evaluation of Wild Yam (Dioscorea spp.) Tubers of Nepal Food Chem. 82 619–623.Adepoju O T, Boyejo O and Adeniji P O 2017 Nutrient and Antinutrient Composition of Yellow Yam (Dioscorea cayenensis) Products Data in Brief 11 428–431.Wu Z-G, Jiang W, Nitin M, Bao X-Q, Chen S-L and Tao Z-M 2016 Characterizing Diversity Based on Nutritional and Bioactive Compositions of Yam Germplasm (Dioscorea spp.) Commonly Cultivated in China J. Food Drug Anal. 24 367 – 375.Udensi E A, Osebele H O and Iweala O O 2008 The Investigation of Chemical Composition and Functional Properties of Water Yam (Dioscorea alata): Effect of Varietal Differences Pakistan J. Nutrition 7(2) 342-344.Hornick S B 1992 Factors Affecting the Nutritional Quality of Crops Am. J. Altern. Agric. 7 (Special Issue on Soil Quality) 63-68.Lewicki P P 2004 Water as the Determinant of Food Engineering Properties, A Review J. Food Eng. 61 483–495Yeh A-I, Chan T-Y and Chuang G C-C 2009 Effect of Water Content and Mucilage on Physico-chemical Characteristics of Yam (Discorea alata Purpurea) Starch J. Food Eng. 95 106–114.McPherson E and Jane J 1999 Comparison of Waxy Potato with Other Root And Tuber Starches Carbohydr. Polym. 40 57–70.Freitas R A, Paula R C, Feitosa J P A, Rocha S and Sierakowski M R 2004 Amylose Contents, Rheological Properties and Gelatinization Kinetics of Yam (Dioscorea alata) and cassava (Manihot utilissima) starches Carbohydr. Polym. 55 3–8.Barsby T L, Donald A M, Frazier P J, Donald A M, Perry P A and Waigh T A 2001 The Impact of Internal Granule Structure on Processing and Properties in Starch: Advances in Structure and Function p 45-52 (Royal Society of Chemistry, http://dx.doi.org/10.1039/9781847551917-00045)Tattiyakul J, Naksriarporn T and Pradipasena P 2012 X-ray Diffraction Pattern and Functional Properties of Dioscorea hispida Dennst Starch Hydrothermally Modified at Different Temperatures Food Bioproc. Technol. 5 964–971.Savikin-Fodulovic K, Grubisic D, Culafic L, Menkovic N and Ristic M 1998 Diosgenin and Phytosterols Content in Five Callus Lines of Dioscorea balcanica Plant Sci. 135 63–67.Cushnie T. P. T, Cushnie B and Lamb A J 2014 Alkaloids: An Overview of Their Antibacterial, Antibiotic-enhancing and Antivirulence Activities Int. J. Antimicrob. Agents 44 (5) 377-386.Tholl D 2015 Biosynthesis and Biological Functions of Terpenoids in Plants, Biotechnology of Isoprenoids p 63-106 Part of the Advances in Biochemical Engineering/Biotechnology book series (ABE, volume 148).Nagata K, Aistrup G L, Honda H, Shono T and Narahashi T 1999 Modulation of the Nicotinic Acetylcholine Receptor by Dioscorine in Clonal Rat Phaeochlomocytoma (PC12) Cells Pestic. Biochem. Physiol. 64 (3) 157–165.Bhandari M R and Kawabata J 2005 Bitterness and Toxicity in Wild Yam (Dioscorea spp.) Tubers of Nepal Plant Foods Hum. Nutr. 60 129–135, 2005.White W L B , Arias-Garzon D I, McMahon J M and Sayre R 1998 Cyanogenesis in Cassava: The Role of Hydroxynitrile Lyase in Root Cyanide Production Plant Physiol. 116 1219-25.Kumoro A C and Hartati I. 2015 Microwave Assisted Extraction of Dioscorin from Gadung (Dioscorea hispida Dennst) Tuber Flour, Procedia Chem. 14 47 – 55.